Clinical Uses of Fructooligosaccharides for Gastrointestinal health in the Pediatric Population - Pournami, Femitha; Ahmad, Ghazi Sharique; Kalawadia, Nayankumar Rameshchandra; Kanithi, Ravishankar; Hazra, Samik; Hemrajani, Satyen Kanhiyalal; Bhatnagar, Shrish; Rahul, Preethi (Indian Journal of Child Health, 2022)
Fructooligosaccharides (FOS) are non-digestible carbohydrates that are one of the major classes of bifidogenic oligosaccharides. Studies find that prebiotics such as FOS display health benefits pertaining to but not restricted to the gastrointestinal tract of an infant. This review article aims to discuss the therapeutic potential of FOS for different pediatric gut conditions. FOS in varying concentration has been found to prevent constipation and soften stools; reduce the incidence and severity of diarrhoea; alleviate GI discomfort symptoms such as vomiting and regurgitation. Infants and children seem to tolerate both short and long chain FOS molecules well. Although FOS is beneficial for infant and child health, there is still a need for rigorous clinical trials and long term follow up studies to understand if FOS supplemented in infancy can confer long term effects in adulthood.